Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find the solution of each of the following initial value problems:

$$a) y''-5y'+6y=0 \space \space \space \space \space \space y(1)=e^2 \space \space y'(1)=3e^2$$

$$b) y''-6y'+9y=0 \space \space \space \space \space \space y(0)=0 \space \space y'(0)=5$$

$$c) y''+4y'+5y=0 \space \space \space \space \space \space y(0)=1 \space \space y'(0)=0$$

I can easily find the general solution for each $a)$ , $b)$ and $c)$, but I'm not entirely sure what to do, or how I use the initial value.

What I have so far, for part $a)$:

$$ y''-5y'+6y=0$$ $$r^2-5r+6=0$$ $$(r-3)(r-2)=0$$ So, the general solution is: $$y=Ae^{2x}+Be^{3x}$$

For part $b)$:

$$ y''-6y'+9y=0$$ $$r^2-6r+9=0$$ $$(r-3)^2=0$$ So, the general solution is: $$y=Ae^{3x}+Bxe^{3x}$$

For part $c)$:

$$r^2+4r+5=0$$ $$\frac{-4 \pm \sqrt{16-4*1*5}}{2}$$ $$-2 \pm i$$ So, the general solution is:


share|cite|improve this question

Take problem a): Plug the initial values into the general solution to get 2 equations in 2 unknowns, A and B. Solve them for A and B. Proceed the same way for the other problems.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.